2022
DOI: 10.3390/nano12111848
|View full text |Cite
|
Sign up to set email alerts
|

The Scalable Solid-State Synthesis of a Ni5P4/Ni2P–FeNi Alloy Encapsulated into a Hierarchical Porous Carbon Framework for Efficient Oxygen Evolution Reactions

Abstract: The exploration of high-performance and low-cost electrocatalysts towards the oxygen evolution reaction (OER) is essential for large-scale water/seawater splitting. Herein, we develop a strategy involving the in situ generation of a template and pore-former to encapsulate a Ni5P4/Ni2P heterojunction and dispersive FeNi alloy hybrid particles into a three-dimensional hierarchical porous graphitic carbon framework (labeled as Ni5P4/Ni2P–FeNi@C) via a room-temperature solid-state grinding and sodium-carbonate-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Wang's group has recently reported that the core-shell structure of Au@NiCo 2 S 4 core-shell NPs could result in a higher proportion of high-valance Ni/Co cations and improve its electronic conductivity, which collectively enhances its OER catalytic performance [20]. In addition, a great number of the heterostructures have also been fabricated for an improved electronical performance, such as CoP/FeP 4 [21], Co 9 S 8 /CoO/NC [22], CoFeS 2 @CoS 2 [23], Ni-P-S@FeOOH/CC [24], Ni 5 P 4 /Ni 2 P-FeNi [25], and MnO-OVs/NCNTs [26].…”
Section: Introductionmentioning
confidence: 99%
“…Wang's group has recently reported that the core-shell structure of Au@NiCo 2 S 4 core-shell NPs could result in a higher proportion of high-valance Ni/Co cations and improve its electronic conductivity, which collectively enhances its OER catalytic performance [20]. In addition, a great number of the heterostructures have also been fabricated for an improved electronical performance, such as CoP/FeP 4 [21], Co 9 S 8 /CoO/NC [22], CoFeS 2 @CoS 2 [23], Ni-P-S@FeOOH/CC [24], Ni 5 P 4 /Ni 2 P-FeNi [25], and MnO-OVs/NCNTs [26].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, considerable efforts have been made to explore Earth-abundant and highefficiency transition metal-based OER catalysts, including layered double hydroxides (LDHs) [4], metal oxides [5], phosphides [6], selenides [7], sulfides [8], nitrides [9], and so on. Among them, transition-metal phosphides (TMPs) have been considered as promising candidates for alkaline OER catalysis because of their good electrical conductivity with metalloid characteristics and remarkable durability in working conditions with strong alkaline electrolytes and theoretically outstanding electrochemical catalytic behaviors [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%